The effects of process management as a mediating variable in the relationship between operational capabilities and halal food manufacturing firm performance / Mohamad Norjayadi Tamam - Tamam, Mohamad Norjayadi (2020)
The Resource-Based View (RBV) is a dominant paradigm in operation management in explaining the differences in business performance which is influenced by heterogeneous resources across the firm. According to RBV, the strategy pillar that are related to four resources characteristic; valuable, rare, inimitable, and non-substitutable form the primary basis for competition between firms. Therefore, firms who are able to reconfigure the resources strategically in their operations will have a competitive advantage against their competitors. In relation to the Halal industry in Sarawak, the problems related to competitive advantage are considered lower compared with the similar industry in West Malaysia. There are limited numbers of Halal certified companies in Sarawak which are capable of exporting their products. Moreover, the number of Halal certified companies In Sarawak based on Halal Directory by Matrade (2013) indicate that there are only 10 Sarawak companies out of 249 Halal food product exporters in the database. Lack of capabilities in the industry influence the performance of halal food manufactures in Sarawak particularly Bumiputera companies. This research contributes to further insights related to operational capabilities in Halal food manufacturing industry. The critical dimensions of Halal operational capabilities will be identified in relation to the firm performance as well as process management roles as a mediator in explaining the relationship between the two variables. The objectives of this study are to determine the dimensions of operational capabilities affecting Halal food manufacturing firm’s performance. Additionally, the current study investigates direct and indirect effect of operational capabilities and Halal firm’s performance with the inclusion of process management as the mediator. The study employs a quantitative approach to investigate and explain the effect of operational capabilities and the role of process management as a mediator on perceived halal food manufacturing firm performance. A non-probability purposive sampling technique was utilized based on data collected from halal certified companies in Sarawak. The data was keyed in using IBM SPSS Statistic Verson 22 statistical software and the analysis is performed using SmartPLS software. The result found that that operational capability has no effect on halal firm performance, however, it shows significant relationship on process management. This implies that operational capabilities alone do not contribute to halal firm performance. Having the mediation effect of process management between operational capabilities and halal firm performance indicate the important link between both relationships. Implementation of process management practices by the company would lead to better firm performance. Hence, concerted effort from the industry and relevant authorities regardless of state or federal levels is encouraged to work together to inculcate the Process Management in the operation.